Antifungal action and induction of resistance by Bacillus sp. strain YYC 155 against Colletotrichum fructicola for control of anthracnose disease in Camellia oleifera - Zhou, Aiting; Wang, Fang; Yin, Jiabi; Peng, Ruiqi; Deng, Jia; Shen, Dezhou; Wu, Jianrong; Liu, Xiaoyun; Ma, Huancheng (Frontiers in Microbiology, 2022)
Anthracnose disease caused by Colletotrichum fructicola, is a serious disease that can afflict the Camellia oleifera. Biological control is a rapidly growing approach for the management of plant diseases. In this study, we investigated the bio-control efficiency and the defence responses of an endophytic Bacillus tequilensis strain YYC 155 which was isolated from root nodule of the Crotalaria pallida against anthracnose disease, caused by C. fructicola in C. oleifera. B. tequilensis YYC 155 exhibited significant inhibitory activity against anthracnose disease, caused by C. fructicola in C. oleifera. YYC 155 can secrete extracellular hydrolases, such as chitinase and β-1, 3-glucanase, produces lipopeptides that are antimicrobial, and forms strong biofilms. In addition, treatment with YCC 155, the cell membranes of C. fructicola was injured and the leakage of cell contents from mycelia of the pathogen was increased. Spraying 1×107 cells mL-1bacterial suspension of YYC 155 on C. oleifera leaves, enhanced the activity of key enzymes in C. oleifera associated with the phenylpropanoid pathway and increased the content of phenolic compounds and flavonoids. Results of our study indicate that B. tequilensis YYC 155 may potentially represent an effective biocontrol agent against anthracnose disease in C. oleifera.